Development of drop number performance for estimate hydraulic jump on vertical and sloped drop structure - Sholichin, M.; Akib, S. (Academic Journals, 2010)
Hydraulic jumps primarily serve to dissipate the excess energy of flowing water downstream of hydraulic structures, such as spillways, weir, sluice gates etc. This type of jump is of practical importance when tail water depth is inadequate to give a good jump. The research conducted at the hydraulics laboratory aimed to obtain suitability of drop number (D) and an estimated hydraulic jump using the drop number. The objective was to obtain the affectivities of application of D on vertical drop and sloped drop structures and to develop the model equation for the sloped drop structure. The hydraulic laboratory conducted research on a hydraulic rectangular flume. Results showed that the D equation could predict drop length (L(d)), and hydraulic jump length (L(j)) for vertical drop structures; however, the equation could not estimate the hydraulic jump length for sloped drop structure. Therefore, development of a D equation that could be used to estimate hydraulic jump for sloped drop structures, with analysis of non dimensional relationships based on mathematical equations, was needed. These equations have correlation regression with a range between 60 - 87% and relative error with a range between 5 - 13%.